THE 50th ANNIVERSARY OF THE DEPARTMENT OF ORTHOPEDIC RHEUMATOLOGY, V.A. NASONOVA RESEARCH INSTITUTE OF RHEUMATOLOGY: RESULTS AND PROSPECTS - V. P. Pavlov (Научно-практическая ревматология, 2015)
The paper describes basic steps in the establishment (1964) and development of orthopedic rheumatology and discusses its present-day status. The 50th anniversary of this discipline that is a component of modern rheumatology was celebrated in 2014. In connection with such a remarkable date the author sums up some results of the scientific and practical activities of the orthopedic rheumatologists of the V.A. Nasonova Research Institute of Rheumatology and considers the prospects for further research developments, the possible evolution of minimally invasive surgery (arthroscopic technology for the treatment of large and small joints), and the issues of rehabilitation in a wide range of rheumatic diseases, by applying high technology.